RANCANG BANGUN APLIKASI E-VEGETABLES MENGGUNAKAN FLUTTER DI KOTA BATAM - Kevin; Saut Pintubipar Saragih (Computer Science and Industrial Engineering, 2025)
Housewives are responsible for managing kitchen needs, regularly shopping for vegetables to meet daily food ingredient requirements. Vegetable shops run by the community serve as one of the alternatives for housewives to buy vegetables. However, they often face difficulties in obtaining information about the availability of vegetable products in stores or shops, as well as price information. This study aims to design and develop an e-vegetables application. The application helps buyers access store information and place orders online, while also enabling sellers to reach a wider consumer base. The method used in this study is the Rapid Application Development (RAD) method, which involves stages such as requirement planning, system design, development, and implementation. The application is designed using UML (Unified Modeling Language) for diagram modeling and Figma for user interface design. It is built in Android operating system using Flutter for the frontend, Node.js for the backend, and MongoDB as the database. The results of this study show that the e-vegetables application facilitates buyers in obtaining vegetable information and placing orders efficiently.